2016
DOI: 10.18632/oncotarget.9806
|View full text |Cite
|
Sign up to set email alerts
|

The reverse-mode NCX1 activity inhibitor KB-R7943 promotes prostate cancer cell death by activating the JNK pathway and blocking autophagic flux

Abstract: We explored the effects of KB-R7943, an inhibitor of reverse-mode NCX1 activity, in prostate cancer (PCa). NCX1 was overexpressed in PCa tissues and cell lines, and higher NCX1 levels were associated higher PCa grades. At concentrations greater than 10 μM, KB-R7943 dose-dependently decreased PC3 and LNCaP cell viability. KB-R7943 also increased cell cycle G1/S phase arrest and induced apoptosis in PC3 cells. KB-R7943 increased autophagosome accumulation in PCa cells as indicated by increases in LC3-II levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Autophagy facilitates cellular survival by enabling cancer cells to grow under the adverse environment [38]. An increasing number of preclinical studies have demonstrated that targeting autophagy is a promising new strategy for many cancer therapies [12][13][14][15][16][17]. HCQ is the only clinically-approved autophagy inhibitor, however its effects explored in the current clinical trials for a variety of cancers are still not satisfactory [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy facilitates cellular survival by enabling cancer cells to grow under the adverse environment [38]. An increasing number of preclinical studies have demonstrated that targeting autophagy is a promising new strategy for many cancer therapies [12][13][14][15][16][17]. HCQ is the only clinically-approved autophagy inhibitor, however its effects explored in the current clinical trials for a variety of cancers are still not satisfactory [18].…”
Section: Discussionmentioning
confidence: 99%
“…One category targets the early stage of autophagy to suppress autophagy induction, such as the frequently-used 3-methyladenine (3-MA), wortmannin, LY294002 [5,6], and the newly discovered spautin-1 [7], SBI-0206965 [8], SAR405 [9], NSC185058 [10], etc. The other works on the later stage of autophagy via blocking autophagosome-lysosome fusion and/or inhibiting autolysosome degradation, including the commonly-used chloroquine (CQ), hydroxyl CQ (HCQ), and bafilomycin A 1 [5,6], as well as the newly discovered lucanthone [11], Lys05 [12], oblongifolin C [13], liensinine [14], ARN5187 [15], elaiophylin [16], KB-R7943 [17], etc. Unfortunately, the high toxicity of most autophagy inhibitors limits their clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of studies have shown that the induction of autophagy synergistically enhanced the chemotherapeutic effect of many cytotoxic drugs on cancer cells. 36,37 It has been reported that the relationship between autophagy and apoptosis can be divided into three types: autophagy and apoptosis do not interfere with each other, autophagy induced apoptosis, autophagy inhibited apoptosis. 38 In this study, it was found that JHC-4 significantly increased the cytotoxicity of paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interpretation of the reverse-mode NCX cannot rely solely on proofs using this blocker. In prostate cancer cells, KB-R7943 was reported to inhibit all the processes connected with cell growth, cell cycle progression, and migration; and it has also been shown to induce apoptosis [ 41 ].…”
Section: In Solid Tumors Ncx1 Operates Predominantly In Reverse Momentioning
confidence: 99%
“…As already mentioned, the NCX operates in reverse mode in some cancer cells [ 41 , 42 , 43 ]. Recently it was shown that in hypoxic tumors NCX1 forms a metabolon with other proteins, which enhances the effectiveness of proton extrusion [ 25 , 43 ].…”
Section: In Solid Tumors Ncx1 Operates Predominantly In Reverse Momentioning
confidence: 99%